Unearthing roots - Lim, Ling Ern (Nanyang Technological University, 2020)
Unearthing Roots is a project that aims to increase the awareness of Traditional Chinese Medicine (TCM) in Singapore. The concept of Unearthing Roots revolves around creating opportunities for the younger generation in Singapore to know more about TCM through an interactive installation and mobile application which are designed to bridge the gap between them. The installation consists of three main segments:The first is an interactive physical display of a range of selected herbs and common kitchen ingredients widely available and affordable in Singapore. The set-up will include visible categorisation of these individual featured display for each of the common illness explored in the project.The second is an educational mobile application which can be accessed by the tablet on display as well as on all other mobile devices with the scanning of the QR code provided. The APP offers an educational experience where the user can explore and customise their own virtual cup of healthy tea and/or a bowl of dessert by choosing the respective herb or kitchen ingredient offered through the gameplay.The third will be providing tangible takeaways from the installation. The audience will be able to select and keep an Unearthing Roots incentive pack which contains palm sized cards and tea packets packed with actual ingredients in it.The cards contain bite-sized information about the herbs and kitchen ingredients meant to relieve a common illness in accordance with the tea packet provided along with it.